The Position of Victims in the Restorative Justice Mechanism under the New Criminal Code: Between Legal Protection and Substantive Justice - Flora, Henny Saida; Simarmata, Berlian (PDIH Untag Semarang, 2026)
This study aims to analyze the potential problems in the implementation of restorative justice concerning the position of victims within the criminal justice system in Indonesia, as well as to formulate an ideal reconstruction of the victim’s position in restorative justice under the New Criminal Code based on justice and Pancasila values. The research employs a normative legal method with statutory, conceptual, philosophical, and comparative approaches. Legal materials are obtained through library research, consisting of primary, secondary, and tertiary sources, and are analyzed qualitatively using legal interpretation techniques. The findings reveal that the implementation of restorative justice still faces several challenges, including inadequate regulation concerning victims’ rights and protection, regulatory disharmony, the dominance of law enforcement authorities, and a legal culture that has not fully supported substantive justice. These conditions result in victims not being positioned as primary subjects but rather remaining in a vulnerable position within the criminal case resolution process. As a solution, this study proposes an ideal reconstruction of the victim’s position through strengthening legal substance that affirms victims’ rights, harmonizing regulations, limiting the discretion of law enforcement officials, and reinforcing a legal culture oriented toward victim recovery. This reconstruction is grounded in the values of Pancasila, particularly just and civilized humanity and social justice. Therefore, restorative justice is expected to function not only as a mechanism for resolving cases but also as an instrument for achieving substantive justice and comprehensive recovery of victims’ rights.